Circulating semaphorin-4D and plexin-B1 levels in postmenopausal women with low bone mass: the 3-month effect of zoledronic acid, denosumab or teriparatide treatment. (March 2015) - Anastasilakis, Athanasios D; Polyzos, Stergios A; Makras, Polyzois; Gkiomisi, Athina; Sakellariou, Grigorios; Savvidis, Matthaios; Papatheodorou, Athanasios; Kokkoris, Panagiotis; Terpos, Evangelos
<x xml:space="preserve">Abstract</x> Objective: The evaluation of circulating semaphorin-4D (sema4D) and plexin-B1 in postmenopausal women with low bone mass and the effect of antiresorptive or osteoanabolic treatment. Methods: Serum samples were obtained from postmenopausal women with low bone mass at baseline and 3 months after zoledronic acid infusion (n = 30), denosumab injection (n = 30) or teriparatide initiation (n = 28) and from controls matched for age, age at menopause and body mass index (n = 30) at the same time points. Main outcome measures: Circulating sema4D and plexin-B1. Results: Circulating sema4D increased following denosumab (p = 0.026), whereas decreased following teriparatide (p = 0.013). Sema4D/plexin-B1 ratio increased following denosumab (p = 0.004). At baseline, sema4D and plexin-B1 levels were higher in patients pre-treated with bisphosphonates compared to naïve ones (p < 0.001 and p = 0.001, respectively). In bivariate correlations sema4D was inversely correlated with serum carboxyterminal telopeptide of type 1 collagen (rs -0.282, p = 0.002), intact parathyroid hormone (rs -0.388, p < 0.001) and 25(OH)D (rs -0.316, p < 0.001), whereas there was a trend towards correlation with lumbar spine bone mineral density (rs -0.191, p = 0.053). Conclusions: Sema4D levels are independently associated with previous bisphosphonate treatment, intact parathyroid hormone and 25(OH)D levels. Denosumab and teriparatide seem to exert an opposite effect on circulating sema4D levels. Further studies are needed to evaluate whether sema4D mediates the coupling effect that occurs following both antiresorptive and osteoanabolic treatment.